2021
DOI: 10.1002/hbm.25392
|View full text |Cite
|
Sign up to set email alerts
|

Vascular origins of low‐frequency oscillations in the cerebrospinal fluid signal in resting‐state fMRI: Interpretation using photoplethysmography

Abstract: In vivo mapping of cerebrovascular oscillations in the 0.05-0.15 Hz remains difficult.Oscillations in the cerebrospinal fluid (CSF) represent a possible avenue for noninvasively tracking these oscillations using resting-state functional MRI (rs-fMRI), and have been used to correct for vascular oscillations in rs-fMRI functional connectivity. However, the relationship between low-frequency CSF and vascular oscillations remains unclear. In this study, we investigate this relationship using fast simultaneous rs-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 92 publications
3
18
0
Order By: Relevance
“…Furthermore, the NT1 group had lower Var frac in MREG card in the anterior corni of the lateral ventricles. Since the cardiac pulsation is known to drive CSF flow also in the ventricular system 71 – 73 , these present results may reflect the altered flow of CSF along the aqueduct and through the lateral ventricles in narcolepsy type 1 patients. A recent study showed that interstitial brain volume increases during sleep, while noradrenaline activity decreased this volume during wakefulness, indicating that declining noradrenaline-driven vasomotor tone during sleep is conducive to CSF flow through the brain 25 .…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, the NT1 group had lower Var frac in MREG card in the anterior corni of the lateral ventricles. Since the cardiac pulsation is known to drive CSF flow also in the ventricular system 71 – 73 , these present results may reflect the altered flow of CSF along the aqueduct and through the lateral ventricles in narcolepsy type 1 patients. A recent study showed that interstitial brain volume increases during sleep, while noradrenaline activity decreased this volume during wakefulness, indicating that declining noradrenaline-driven vasomotor tone during sleep is conducive to CSF flow through the brain 25 .…”
Section: Discussionmentioning
confidence: 70%
“…Better HRV parameters compared to sleep may indicate that the "humming" state is unique and can sustain respiratory components through a resonance frequency even lower than 0.1 Hz. The use of sound vibrations at the lower frequency may have a potentially influencing role in CSF flow that could be studied further [ 14 , 32 ]. The lower stress index and SDNN confirm the unique RR variations during humming.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing stress is one of the critical enablers for increased cognition. Recent research highlighting the area of cerebrospinal fluid (CSF) flow further supports this claim [ 14 , 15 ]. The use of sound vibration further enhances cognition, focus, and attention [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a transfer of LF waves via the IC arterio–venous capacitive coupling [ 14 ] would be rather more sensitive to the systolic AF modulation, since the major role of the capacitive coupling is compensating the systolic arterial water-hammer effect. Further evidence supporting this hypothesis is the poor presence of LF waves in the CSFF series [ 27 ]. Clearly, the CSF compartment is only capacitively coupled to AF and VF.…”
Section: Discussionmentioning
confidence: 99%